2011
DOI: 10.4103/0970-0218.80793
|View full text |Cite
|
Sign up to set email alerts
|

Study of childhood obesity among school children aged 6 to 12 years in union territory of Puducherry

Abstract: Objective:To study the prevalence of obesity and overweight among school children in Puducherry. To identify any variation as per age, gender, place of residence and type of school.Setting and design:Secondary data analysis of a school-based cross sectional study in all the four regions of Puducherry.Materials and Methods:Children between 6 and 12 yrs were sampled using multistage random sampling with population proportionate to size from 30 clusters. Anthropometric data (BMI) was analyzed using CDC growth cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 8 publications
(9 reference statements)
5
42
1
1
Order By: Relevance
“…Mahajan and his coworkers in a study on school children in Union Territory of Puducherry, the prevalence of overweight and obesity was 4.98% and 2.24% respectively. [15] A similar finding was reported from another study in Kerala by Raj et al, indicated an increasing prevalence of overweight and obesity from 4.94% and 1.26% in 2003 to 6.57% and 1.89% in 2005 with particular rise in the age group 5-11 yrs. Andhra Pradesh had 2nd highest prevalence of overweight (5.68%), and lowest prevalence of obesity (0.57%).…”
Section: Discussionsupporting
confidence: 75%
“…Mahajan and his coworkers in a study on school children in Union Territory of Puducherry, the prevalence of overweight and obesity was 4.98% and 2.24% respectively. [15] A similar finding was reported from another study in Kerala by Raj et al, indicated an increasing prevalence of overweight and obesity from 4.94% and 1.26% in 2003 to 6.57% and 1.89% in 2005 with particular rise in the age group 5-11 yrs. Andhra Pradesh had 2nd highest prevalence of overweight (5.68%), and lowest prevalence of obesity (0.57%).…”
Section: Discussionsupporting
confidence: 75%
“…A study has shown similar results. (10) The combined prevalence of overweight and obesity is higher in boys of classes II (Age about 7 years). This observation can be explained on the basis that boys are favoured over girls for access to calorie-dense food.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in the study of age groups in studies conducted in different parts of India. (9,10) Though different parameters and growth references were used to define overweight and obesity, higher prevalence of it has been reported from rural part of Maharashtra also. (11,12) The prevalence of overweight and obesity in young boys has been reported to be 19.9% and 5.7% respectively using International Obesity Task Force (IOTF) criteria in a study conducted in urban Pune.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Indian studies prevalence was high which may indicate raising trend in the prevalence. [11][12][13] And also in most of these studies CDC charts was used for assessing BMI Status where as we Prevalence of obesity and overweight was more among the younger children, overweight was more prevalent among males and obesity among females.…”
Section: Prevalence Of Obesitymentioning
confidence: 99%